Os espaços da fé: um estudo sobre o campo religioso na perspectiva da reliosidade popular - Lopes, André Camargo (Universidade Estadual de Londrina, 2018)
In view of the continuous change in the Brazilian religious field, this article is aimed at analyzing, through interviews and field observation, the maintenance and the ritual practices of the two major religious groups in the daily life of a small popular neighborhood in Londrina, state of Paraná. The discussion includes the circularities between the official discourse and the practices of religious agents, the maintenance of traditional popular Catholicism, the observation of a regular worship service, and an analysis of the elements that constitute the neighborhood’s religious identity of the Assembléia.